2011
DOI: 10.1098/rstb.2010.0189
|View full text |Cite
|
Sign up to set email alerts
|

Navigation by light polarization in clear and turbid waters

Abstract: Certain terrestrial animals use sky polarization for navigation. Certain aquatic species have also been shown to orient according to a polarization stimulus, but the correlation between underwater polarization and Sun position and hence the ability to use underwater polarization as a compass for navigation is still under debate. To examine this issue, we use theoretical equations for per cent polarization and electric vector (e-vector) orientation that account for the position of the Sun, refraction at the air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…We found that refraction affects the LPPF mainly at low sun elevations near sunrise or sunset, changing the location of the neutral points from their position in the exact F/B directions in the theoretical Rayleigh LPPF, in agreement with Adams and Gray [25], although the effect of refraction on the location of the neutral points may not be as significant when multiple scattering occurs [14]. This is important because refraction may be used as a reference for navigation by polarization-sensitive marine species, as the refraction angle in water limits the e-vector orientation in clear conditions at viewing angles around the horizon [41]. Refraction increases polarization mainly in the F/B scattering directions, which may also be useful for polarization-based contrast detection (i.e., the polarization difference between a target and its background; see [42,43]).…”
Section: Discussionsupporting
confidence: 71%
“…We found that refraction affects the LPPF mainly at low sun elevations near sunrise or sunset, changing the location of the neutral points from their position in the exact F/B directions in the theoretical Rayleigh LPPF, in agreement with Adams and Gray [25], although the effect of refraction on the location of the neutral points may not be as significant when multiple scattering occurs [14]. This is important because refraction may be used as a reference for navigation by polarization-sensitive marine species, as the refraction angle in water limits the e-vector orientation in clear conditions at viewing angles around the horizon [41]. Refraction increases polarization mainly in the F/B scattering directions, which may also be useful for polarization-based contrast detection (i.e., the polarization difference between a target and its background; see [42,43]).…”
Section: Discussionsupporting
confidence: 71%
“…To date, it was only known that polarization sensitivity is used by cuttleWsh for predation (Shashar et al 2000) and possibly in communication (Shashar et al 1996;Boal et al 2004). Squid (Jander et al 1963) exhibit spontaneous preferential swimming direction relative to the e-vector orientation, like some species of crustaceans (Horvath and Varju 2004;Sabbah et al 2005;Lerner et al 2011). CuttleWsh learn to use landmarks and the e-vector orientation in parallel.…”
Section: Discussionmentioning
confidence: 96%
“…For much of the day and for most conditions, scattering from particles in the water column provides a predominantly horizontally polarized light field [35][36][37][38]. The result is that any animal possessing a vertical polarizing analyser, looking into this strongly (20-40%) horizontally polarized illumination, will be able to detect some objects more effectively against the resultant 'dark field' background provided by the vertical analysis of horizontally polarized light.…”
Section: Discussionmentioning
confidence: 99%